Communication yearbook 14 - Anderson, James A. (Communication yearbook, 2012)
Covers literature reviews that advance knowledge and understanding of communication systems, processes, and impacts across the discipline. Sponsored by the International Communication Association, this volume provides a forum for the exchange of interdisciplinary and internationally diverse scholarship relating to communication in its many forms.